Polyhydramnios is associated with postnatal dysphagia determining short-term prognosis of the newborn with 22q11.2 deletion syndrome - A case series analysis - Tamae Nabeshima; Tatsuya Fujii; Takeshi Nagamatsu; Ayako Hashimoto; Takahiro Seyama; Kaori Kubota; Seisuke Sayama; Toshio Nakayama; Keiichi Kumasawa; Takayuki Iriyama; Yutaka Osuga; Tomoyuki Fujii (Elsevier, 2020)
Objective: We experienced a case of 22q11.2 deletion syndrome (22qDS), with severe polyhydramnios, and dysphagia, which prompted us to review prognosis in neonates with 22qDS, with a focus on dysphagia. Case report: A patient was referred to our hospital at 35 gestational weeks because of polyhydramnios. After amniotic fluid reduction, labor was induced at 38 weeks. The neonate had serious dysphagia, and 22qDS was diagnosed postnatally by fluorescent in situ hybridization analysis. This prompted a retrospective analysis of 9 cases with 22qDS experienced in our facility. Three out of these nine cases showed polyhydramnios, and had severe dysphagia postnatally. In total, 4 cases had dysphagia, while mortality was observed in 2 of these 4 cases. Additionally, 5 cases without dysphagia had normal development and no major complications. Conclusion: Polyhydramnios associated with postnatal dysphagia might be a risk factor related to short-term prognostic outcomes in newborns with 22qDS.